Construction of self-representations in maltreated children and adolescents: parents’ influence within the Looking-Glass Self - Silva, C. S.; Calheiros, M. M. (XIV EUSARF International Conference: Shaping the future, 2016)
Several theorists have proposed that children develop their self-representations based on their experiences with caregivers (e.g., Bretherton, 1991, 1992; Cassidy, 1990). Thus, the origins of negative working models of self in maltreated populations can be viewed as emanating from harmful caregiving experiences. In fact, several studies have found that maltreated children have less positive self-concepts than non-maltreated children (e.g., Bolger, Patterson, & Kupersmidt, 1998; Toth, Manly, & Cicchetti, 1992). However, research on the construction process of children/adolescents’ self-representations (SR) in the context of maltreatment has been sparse. According to the Looking Glass Self Hypothesis (LGSH; Cooley, 1902; Nurra & Pansu, 2009), individuals’ SR stem from interactions with significant others, reflecting associations between: what others think of them (i.e., significant others’ actual appraisals; SAA), individuals’ perception of others’ appraisals of them (i.e., significant others’ reflected appraisals; SRA), and SR. Yet, even though associations between SRA and SR, associations between SAA and SR and between SRA and SRA have not been consistently verified (Shrauger & Schoeneman, 1979). This study extends past work, by testing the mediating role of SRA in associations between SAA and SR (i.e., LGSH) in the context of child/adolescent maltreatment experiences. Participants were 214 children and adolescents (51.6% boys), 6-16 years old (M=11.86), referred to the children and youth protection committees, and their parents. Maltreatment was evaluated by the committees’ professionals responsible for the participants’ files, through a questionnaire evaluating maltreatment experiences. Self-representations were measured through the Self-representation Questionnaire (Martins, 2013), which was adapted do measure the other LGSH elements – SAA and SRA. Structural equation modelling analyses showed that, controlling for maltreatment effects, significant mediation effects of SRA between SAA and youths’ SR were found for all the SR dimensions evaluated, supporting the LGSH. In addition, results showed significant negative indirect effects of total maltreatment on instrumental and social SR, through mothers’ reflected appraisals on those dimensions. Significant negative total effects of maltreatment on instrumental and social MRA and SR were also found. Findings emphasize the importance of the role of SRA on maltreated youths’ SR construction process and provide useful clues to incorporate in prevention and intervention with vulnerable youth and their parents. From a pragmatic point of view, these results provide useful clues to incorporate in intervention with these vulnerable children and adolescents and their parents. Namely, the findings highlight the need to help children develop the capacity to enter into positive close relationships and to value themselves, and this goal would be advanced through therapeutic strategies designed to address their representational world. Interacting with caregivers who emphasize children’s and adolescents’ negative attributes may result in the consolidation of a self-negativity bias in them (Fischer & Ayoub, 1994). Therefore, parents should be aware not only of what they do and say to their children, but also of the way children understand, perceive and interpret those beliefs and behaviours as it affects their subsequent adjustment outcomes. In terms of positive outcomes, parents may promote positive reflected appraisals and self-appraisals, positive expectancies, and encouragement and thus contribute to their children’s positive adjustment outcomes.